2023
DOI: 10.1094/mpmi-10-22-0223-cr
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Pseudomonas-Assisted Plant Nitrogen Uptake: Opportunities for Modern Agriculture

Abstract: Pseudomonas spp. make up 1.6% of the bacteria in the soil and are found throughout the world. More than 140 species of this genus have been identified, some beneficial to the plant. Several species in the family Pseudomonadaceae, including Azotobacter vinelandii AvOP, Pseudomonas stutzeri A1501, Pseudomonas stutzeri DSM4166, Pseudomonas szotifigens 6HT33bT and Pseudomonas sp. K1 can fix nitrogen from the air. The genes required for these reactions are organized in a nitrogen fixation island, obtained via horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…These findings also highlight differences in endophyte community composition between regions, with specific genera being more abundant in specific regions. Pseudomonas belongs to the phylum Proteobacteria, and previous studies have shown that Pseudomonas can produce siderophores 55 , dissolve phosphate 56 , fix nitrogen 57 , and transport soil nutrients into plants to promote plant growth. grow and protect plants against pathogenic bacteria 58 , suggesting that Pseudomonas species, which are dominant in S. chamaejasme , may play an important role in S. chamaejasme growth and disease resistance, thereby enhancing its ability to compete for habitat.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also highlight differences in endophyte community composition between regions, with specific genera being more abundant in specific regions. Pseudomonas belongs to the phylum Proteobacteria, and previous studies have shown that Pseudomonas can produce siderophores 55 , dissolve phosphate 56 , fix nitrogen 57 , and transport soil nutrients into plants to promote plant growth. grow and protect plants against pathogenic bacteria 58 , suggesting that Pseudomonas species, which are dominant in S. chamaejasme , may play an important role in S. chamaejasme growth and disease resistance, thereby enhancing its ability to compete for habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, many different aminotransferases distribute the amino group within the various amino acids and later into the whole plant metabolism. Thus, it was interesting to analyze the amino acid profile in the plants with and without fungal colonization as also postulated for interactions with beneficial bacteria [33]. The results obtained show clearly the N starvation effect on the Arabidopsis plants.…”
Section: Mortierella Hyalina Restored the Amino Acid Homeostasis In A...mentioning
confidence: 98%
“…The sample element amounts were scaled against an in-house standard "Ali-j3" (Acetanilide) with δ 15 N values of −1.51 ± 0.1‰ on the δ 15 N AIR-N2 scales. "caf-j3" A (caffeine) sample was analyzed as a quality control with values of −15.46 ± 0.1‰ on the δ 15 N AIR-N2 scales [33]. Linearity, blank and drift corrections were undertaken for each sequence according to Werner and Brand (2001) [40].…”
Section: Isotope Analysismentioning
confidence: 99%
“…Pseudomonas is a universal genus in different ecological niches and exhibits a versatile metabolic capacity [ 9 ]. A number of pseudomonas strains function as PGPRs to protect plants from various pathogens and/or stimulate plant growth [ 10 , 11 , 12 , 13 , 14 , 15 ]. For example, P .…”
Section: Introductionmentioning
confidence: 99%
“…For example, P . chlororaphis [ 11 ] and P. protegens [ 10 , 12 ] are non-pathogenic biocontrol agents, while several strains of P. stutzeri [ 14 , 15 ] show strong plant-growth-promoting activities. Bioactive secondary metabolites are the major defense mechanism against pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%